EDUCATIONAL BROADCASTING: PREPAREDNESS, CHALLENGES, AND PROSPECTS OF EBBC TELEVISION - Ononuju Nwankiti, Chukwuemeka; Ogban Obin, Obin; Lynda Ngwu, Ogonnaya; Rose Chime-Nganya, Chioma; Cosmas Nwoga, Chibuzor (African Journal of Social and Behavioural Sciences, 2026)
This study examined the preparedness, challenges, benefits, and prospects of educational broadcasting in Nigeria within the context of 21st-century technological and socio-economic realities, using the Ebonyi Broadcasting Corporation (EBBC) as a case study. Anchored on the Diffusion of Innovation (DOI) theory, the study adopted a mixed-methods approach involving a survey of 385 respondents and interviews with key personnel across EBBC departments. The central argument advanced in this study is that although EBBC recognizes the importance of educational broadcasting, its current level of preparedness reflected in its infrastructure, manpower, funding, and digital adaptation, is insufficient to deliver effective, accessible, and competitive educational programming. Findings revealed persistent structural and operational challenges, including inadequate manpower, insufficient funding, limited public awareness, and technological constraints that undermine the effectiveness and reach of educational broadcasting. While respondents acknowledged the relevance and potential value of EBBC’s educational programs, issues of accessibility, audience penetration, and content effectiveness remain significant. The study contributes to scholarship by providing one of the most comprehensive empirical assessments of a state-owned broadcaster’s readiness for educational broadcasting in Nigeria, applying DOI theory to explain adoption barriers, and proposing actionable pathways for digital transformation, policy alignment, and capacity development. It recommends increased investment in digital infrastructure, enhanced collaboration with educational institutions, improved content development strategies, and targeted digital literacy initiatives. Strengthening these areas will enhance the reach, quality, and impact of educational broadcasting in Nigeria, thereby contributing to national educational development.